2015
DOI: 10.1589/jpts.27.1157
|View full text |Cite
|
Sign up to set email alerts
|

The effects of virtual reality game exercise on balance and gait of the elderly

Abstract: [Purpose] The aim of this study was to examine the effects of ball exercise as a general exercise on the balance abilities of elderly individuals by comparing ball exercise with virtual reality exercise. [Subjects and Methods] Thirty elderly individuals residing in communities were randomly divided into a virtual reality game group and a ball exercise group and conducted exercise for 30 min 3 times a week for 8 weeks. [Results] Step length increased significantly, and the average sway speed and Timed Up and Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
87
1
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(104 citation statements)
references
References 18 publications
1
87
1
15
Order By: Relevance
“…All the four18,2022 remaining studies had a high risk of bias as there was no allocation concealment reported by any of the studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the four18,2022 remaining studies had a high risk of bias as there was no allocation concealment reported by any of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining three studies2022 had an unclear risk of bias as there was insufficient information to make a judgment.…”
Section: Resultsmentioning
confidence: 99%
“…Exergames (EXG) require users to utilize physical and motor skills (PMS), such as: endurance, motor coordination, strength, balance and speed of movement (11); with its ef icacy in improving these abilities in patients undergoing therapy having been proven, particularly in the recovery of upper limb function after a stroke (12) and improved gait and balance in older adults (10). However, few studies have veri ied the effects of EXG on healthy adult subjects (10,12).…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have veri ied the effects of EXG on healthy adult subjects (10,12). Park, Lee and Lee (7) found a signi icant improvement in muscular function of the lower limbs (LL) in healthy young adults, after 6 weeks of training (Nintendo Wii Fit ® ), performed 3 times a week, for 40min.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is possible with virtual rehabilitation to manipulate the environment that would be impractical or impossible to create in the real world (Gokeler et al, 2016). In recent years, many different technologies on virtual rehabilitation have been produced and used in research however, existing studies are limited because most of them focus on the balancing ability of the elderly or studied in stroke patients with same systems (Park et al, 2015). Thus, it is necessary to investigate the effects of a new virtual rehabilitation system in patients with Anterior Cruciate Ligament (ACL) Reconstruction.…”
Section: Introductionmentioning
confidence: 99%